Assessment of knowledge, attitudes and practices regarding COVID-19 among pharmacists in Goa - Cacodcar, Jagadish A.; Rataboli, Padmanabh V.; Naik, Sparsh S.; Santos, Karen Dos; Sanil, Mugdha; Mardolker, Anuja A.; Mote, Shivani B. (International Journal Of Community Medicine And Public Health, 2020)
Background: COVID-19 is a highly transmissible and pathogenic viral infection caused by SARS-CoV-2, which emerged in Wuhan, China and became a global pandemic. The aim of our study was to ascertain knowledge, attitudes and practices of pharmacists who are among the Frontline Healthcare Workers involved in infection control and prevention of COVID-19; employing a pre-designed semi-structured questionnaire. Methods: This descriptive cross-sectional study employing a pre-designed semi-structured questionnaire was carried out among 200 pharmacists in Goa, using simple random sampling method. The study period was 1 month during March-April 2020. Results: Out of 200 pharmacists, the name of the disease was known by 87%, mode of transmission by 94.5% and major symptoms of the disease by 61%. Very few (28.5%) participants knew that quarantine is for asymptomatic contacts of the disease. Majority (69%) were aware that persons at risk should be placed under observation for 2 weeks. Only 18% knew that 6 feet constitutes close contact. A large number (93%) were aware of the preventive measures for the disease. Most participants possessed the right attitudes and followed correct practices- 96% were willing to avoid foreign travel, 90% preferred to avoid shaking hands during the ongoing disease transmission, 93% cover their face while coughing/sneezing and 98% maintain good hand hygiene. Conclusions: The knowledge among pharmacists of Goa though limited, was adequate in terms of epidemiology and clinical presentation of the novel disease. They possessed the right attitudes and followed appropriate preventive practices.